EVALUASI STABILITAS FISIKO-KIMIA DAN UJI HEDONIS GEL PEMBERSIH WAJAH ANTIPOLUTAN BUNGA ROSELLA UNGU - Fitri, Hidayah Anisa; Hidayah Anisa, Fitri; Rahman, Fikri Nur; Falahdin, Fadita Iza; Fitriyani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
An evaluation of a cosmetic product containing natural ingredients is important to determine its stability and shelf life. This study aims to evaluate the physicochemical aspects and acceptance of Facial Wash Gel Purple Roselle Flower to asess the quality, effectiveness, safety and acceptance of the product after optimization development. The stability evaluation was carried out by cycle testing methods and accelerated stability testing for its physical (viscosity, pH and dispersal power) and chemical aspect. The chemical aspect determined Total Flavonoid Contents (TFC) using UV-Vis spectrophotometry methods. The data were analyzed statistically using the SPSS program using two-tailed T-Test model for cycle test data and paired T-Test sample for accelerated stability test. The product acceptance evaluation was conducted using hedonistic test. Based on the data , it can be concluded that the optimum formula could still maintain its physical stability in cycle tests and accelerated physico-chemical stability tests. Although there was syneresis and pH increasing (P<0.05) during the test but they were not significantly affected organoleptic and TFC in products (P>0.05). All the physical parameters were still met the requirements of facial cleansing gel. The results of the hedonistic test showed that all panelists liked color, smell, texture, clean and coarse sensations and did not give dryness and irritation after use. However, all panelists rather like the foam characteristics that did not meet expectations. It was likely caused by the panelists' personal perception, experience and understanding of foam in a cleaning product.